Implications of Teacher Competence and Medium of Instruction on the Implementation of Kenyan Sign Language Curriculum in Secondary Schools in Kenya: Analytical Assessment - and Salanwa Ilondanga, Lenod; Oracha, P.; Othuon, Lucas; M.W. Simatwa, Enose; M. Simatwa, E. (2015)
Curriculum implementation is a crucial, difficult and unavoidable phase in curriculum development. It entails putting into practice the officially prescribed courses of study as intended. The way a curriculum is introduced can create a discrepancy between the proposed curriculum and the actual practice in schools. For deaf students to achieve the goals of education there was need to include Kenyan Sign Language in the curriculum. This was attempted in 2007 in standard one, five and form one classes. It was noticeable that this was the same year teachers were called upon to prepare materials and be in-serviced for the implementation. In 2008 there was an outcry of teachers expressing their discomfort in teaching Kenyan sign language without adequate preparations. The purpose of this study therefore, was to examine teacher factors during the implementation of Kenyan sign language curriculum in Kenya. Descriptive survey design was used in the study. The target population comprised of 15 sign language teachers from 4 secondary schools spread out in four districts in Kenya namely; Nyeri, Mumias, Rongo and Bondo. The sample size consisted of 13 teachers. The study employed saturated sampling technique because the population was too small. Data was collected by use of questionnaire, interview schedule and lesson observation checklist. A pilot study was conducted in one of the schools selected through simple random sampling technique. The instruments used in the study were presented to Lecturers in the faculty of Education at Maseno University to ascertain their face validity. Reliability was computed using Cranbach's Alpha which showed 0.361, 0.440, 0.481 and 0.468 for objectives, content, teaching materials and evaluation respectively. Quantitative data was analyzed using descriptive statistics and presented as frequency counts, percentages and charts. Qualitative data was collected, categorized into emergent themes which were reported. Results indicated that teachers had professional certificates, attended in-service courses and had experience; teachers used different media of instruction Based on the findings, this study concluded that although teachers' level of competent was average they needed proficiency examination to improve. Although teachers used Kenya sign language as the language for instruction there was no uniformity in the medium of instruction.